2023
DOI: 10.1002/solr.202300229
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Stress Testing of Perovskite Photovoltaic Modules: Differentiating Degradation Modes with Electroluminescence Imaging

Jackson W. Schall,
Andrew Glaws,
Nutifafa Y. Doumon
et al.

Abstract: Herein, electroluminescence (EL) and thermal imaging are used to examine p-i-n metal halide perovskite (MHP) photovoltaic (PV) mini-modules (MA 0.6 FA 0.4 PbI 3 , 20 cells, 78 cm 2 ) before and after indoor-accelerated stress testing or outdoor deployment. Distinct spatial patterns in the EL images emerge, which depend on the external stress conditions experienced by the mini-module. Imaging results highlight a distribution of dark speckle features that dominate after UV stress, attributed to widespread interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…−71 k*J*mol −1 , indicating that the redox process between SO 2 and I 2 is spontaneous. Previous studies have shown that molecular iodine generation in perovskites under illumination is a common phenomenon and can accelerate the degradation of perovskites under operating conditions 20 , 30 32 . We thus hypothesize that CF 3 SOO ‒ ions can reduce I 2 into I 3 ‒ in the perovskite solutions 20 .…”
Section: Resultsmentioning
confidence: 99%
“…−71 k*J*mol −1 , indicating that the redox process between SO 2 and I 2 is spontaneous. Previous studies have shown that molecular iodine generation in perovskites under illumination is a common phenomenon and can accelerate the degradation of perovskites under operating conditions 20 , 30 32 . We thus hypothesize that CF 3 SOO ‒ ions can reduce I 2 into I 3 ‒ in the perovskite solutions 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Perovskite-based nanomaterials are at the forefront of ECL sensor development due to their excellent optoelectronic properties, 111–114 including direct bandgap, 115 robust defect tolerance, 116 and tunable emission. ECL research in perovskite-based nanomaterials is advancing, showcasing diverse applications and efficiencies across various types of perovskites (detailed in Table 3).…”
Section: Optical Sensorsmentioning
confidence: 99%